Transtorno do desenvolvimento da coordenação em crianças com transtornos do deficit de atenção e hiperatividade: um estudo com um programa de aprendizagem de natação - Damasceno, Leonardo Graffius (2017)
This study aimed to investigate the influences of a swimming learning program on the Developmental Coordination Disorder (DCD), in children with Attention Deficit Hyperactivity Disorder (ADHD). The sample consisted of 05 children, boys, between 7 and 9 years of age, presenting a diagnosis of ADHD of the combined subtype, with comorbidity of DCD (ADHD/DCD). The children (N = 05) were a single group submitted to an aquatic intervention with systematized swimming lessons. The group was submitted for 3 months, to two weekly classes of 50 minutes duration, totaling 23 sessions / meetings. The motor coordination dependent variable (total DCDQ-Brazil score) was evaluated at two points in time - pre and post test. The results regarding the total DCDQ-Brazil test score showed a positive effect between the times, which expresses functional significance to the intervention, approximating the development of the motor coordination of the child with ADHD/DCD of the reference for children with typical development. At least considering our sample, we infer that motor intervention through sport in the form of a Swimming Learning Program contributed to the final performance of children with ADHD/DCD being similar to that of children with typical development. Future studies should be developed with the objective of, for example, investigating the effects of other sports practices on those with a similar diagnosis.